Relación entre el conocimiento y la práctica del autocuidado e hipertensión arterial en los adultos mayores de 35 años del distrito misionero de Chaclacayo de la Iglesia Adventista del Séptimo Día, 2011. - Condori Meza, Deisy (2019)
Objective: The objetive of this study was to determine the relationship between the level of knowledge and self-care practiceswith hypertension in adults older than 35 years of missionary district of Chaclacayo Adventist Church Seventh Day, 2011. Methods: The study was a quantitative non-experimental, descriptive, correlational -causal cross-section in the missionary districtof Chaclacayo, probabilistic sampling, resulting in 123 participants. Results: Regarding the characteristics of the study population el70% and 66.6% of those with hypertension stage 1 and 2 belonged to the female and male, for age, 35% and 66.7% ofthose had hypertension stage 1 and 2 belonged to the age group between35 and 45 and 46 to 56 years. Study regarding the extentof 40% and 66.7% of those with hypertension stage 1 and 2 belonged to the higher grade. In contrast to family history 40% and66.6% of those presenting, hypertension stage 1 and 2, had a family history. With regard to knowledge about the presence ofhypertension 55.0% and 100%of those with hypertension stage 1 and 2, were aware of the presence of hypertension. Accordingto the churches to 28.6% and 20% of those with stage 1 hypertensionbelonged to the churches of the Forest and Chaclacayo, and5% and 10% of those withhypertension, 2 belonged to the churches of Villa Rica Chaclacayo . With respect to the frequency ofhypertension, found that 35% (44) had pre-hypertension, 18.7% (23) hadhypertension stage 1 and 2. Depending on the level ofknowledge of hypertension, found that 55% and 66.7% of those with hypertension stage 1 and 2 had excelente.En good level andthe level of practice with hypertension, found that 75% and 99.9% of those with hypertension stage 1 and 2 were low level toregulate and from poor to good. Conclusions: There is a very weak positive relationship between knowledge and hypertension,as opposed to self-care practices with hypertension, because there is asignificant positive relationship. Also, in relation betweenthe level of knowledge and self-care practices with hypertension show that there is a weak positive relationship.